The One-Child Policy Amplifies Economic Inequality across Generations in China - Yewen Yu; Yi Fan; Junjian Yi (Institute of Labor Economics (IZA), 2020)
This study finds that China's one-child policy (OCP), one of the most extreme forms of birth control in recorded history, has amplified economic inequality across generations in China since its introduction in 1979. Poor Chinese families, whose fertility choices are less constrained by the OCP than rich ones, have more children but invest less in human capital per child. Since human capital is a major determinant of earnings, the income inequality persists and enlarges across generations as a consequence. Based on nationally representative longitudinal household survey data, our estimation results show that the OCP accounts for 32.7%-47.3% of the decline in intergenerational income mobility. The OCP has significant ramifications for Chinese society, not only intragenerationally but also intergenerationally.
Keywords: E24; J13; 330; One-Child Policy; differential fertility; child quantity-quality tradeoff; intergenerational mobility